DEVELOPMENT OF METHODICAL APPROACHES TO THE CREATION OF THE PHARMACOLOGICALLY ACTIVE BANDAGE - Nv, Khokhlenkova; Sm, Kovalenko; Jm, Azarenko; Mv, Buryak (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The results of modern research on the creation of pharmacologically active bandage were generalized. The main components of the development of pharmacologically active dressing (choice of active ingredients, carrier substrate, the method of immobilization, etc.) were determined. Methodological approaches to the creation ofÂ  pharmacologically active bandage were developed. The practical significance of the developed methodological approaches demonstrated by research and development of dressings with thick oak bark extract.